A Rare Case of Alpha-Thalassaemia Intermedia in a Malay patient double heterozygous for a+-Thalassaemia and a mutation in a1 Globin Gene CD59 (GGC GAC) - George, E.; Tan, J.; Azian, A.S.N.; Rahimah, A.; Zubaidah, Z. (Malaysian Medical Association, 2009)
A rare case of thalassaemia-intermedia involving a nondeletion alpha thalassemia point mutation in the Î±1-globin gene CD59 (GGC-GAC) and a deletion Î±+ (-Î±3.7) thalassaemia in which use of high performance liquid chromatography (HPLC) C-gram Hb subtype profile and DNA molecular analysis helped establish the diagnosis.